Improving Tax Audit Quality through Accountability and Professional Experience: The Mediating Role of Information Technology - Ulfa Rabiyah; Dewi Anggraeni; Fitri Fitri; Muhammad Ziaul Haq Bakri (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
The central issue addressed in this research is the inconsistent quality of tax audits and the growing demand for accountability and technological capability in modern audit practices. This study examines the influence of information technology use, accountability, and professional experience on tax audit quality in Indonesia, focusing on tax auditors at the Makassar Tax Service Office (KPP). A quantitative approach was employed using Structural Equation Modeling (SEM) based on survey responses from 125 tax auditors. The results show that accountability significantly enhances audit quality (b = 0.491, p 0.001), while professional experience has no direct effect (b = -0.015, p = 0.890). Accountability and professional experience also significantly influence information technology use (b = 0.244, p = 0.003; b = 0.467, p 0.001), and information technology improves audit quality (b = 0.355, p 0.001). Furthermore, information technology mediates the influence of accountability and professional experience on tax audit quality. These findings highlight that high-quality tax audits rely on auditors’ integrity, responsibility, technical skills, and ability to leverage technology as a supporting resource. This research offers empirical insights into determinants of tax audit quality.